A Prototype MR Compatible Positioning Device for Guiding a Focused Ultrasound System for the Treatment of Abdominal and Thyroid Cancer - Mylonas, Nicos; Damianou, Christakis A. (My University, 2013)
A prototype magnetic resonance imaging (MRI)-compatible positioning device that navigates a high intensity focused ultrasound (HIFU) transducer is presented. The intended application is to treat eventually tumours in the abdominal and thyroid. The positioning device has 3 user-controlled stages that allow access to various targets using a top to bottom coupling approach. Materials and Methods. The positioning device incorporates only MRI compatible materials such as piezoelectric motors, ABS plastic, brass screws, and brass rack and pinion. Results The MRI compatibility and the accuracy of the system were successfully demonstrated in an open MRI scanner. The robot has the ability to accurately move the transducer thus creating discrete and overlapping lesions in rabbit liver in vivo. This simple, cost effective positioning device can be placed mostly on the structure of an open MRI gantry. Due to the size of this positioning device, the proposed prototype in its current form cannot be used in any closed MRI system. The novelty of this positioning device is the MRI compatible design and its intended application which is the treatment of tumors in the abdominal area using focused ultrasound. This system can be utilized in the future to treat patients with cancer in the liver, kidney, pancreas and thyroid provided that the accuracy of the positioning device is greatly improved.